An algebraic model of high-altitude aircraft decompression and emergency descent. Issue 3 (3rd July 2017) - Daidzic, Nihad E.
Abstract: An emergency descent maneuver initiated by pilots shortly after the onset of the decompression recognition was developed for subsonic, supersonic and hypersonic cruisers. Among other findings, the times when a passenger cabin is exposed to altitudes above 25, 000 and 40, 000 ft and the maximum cabin altitude reached are estimated. An airplane descent aerodynamic model was incorporated for high-speed and low-speed high-drag emergency descents. Airplane cabin atmosphere is assumed to be isothermal. The environmental atmosphere is simulated using the NLPAM nonlinear atmospheric model valid up to 47 geopotential kilometers. Rapid and slow decompressions at several discrete cruising altitudes ranging from 12 to 40 km and varying pilot reaction times in initiating the emergency descent were simulated. The main motivation for this work was to estimate times and altitudes a cabin reaches during depressurization for various flight conditions. This model can be utilized in optimizing the emergency-descent piloting techniques, calculating oxygen supplies, evaluating aeromedical factors, estimating harmful exposures to low pressures, and for other important high-altitude aircraft operations.